Development of PIR sensor-based security system and IoT-based esp-32 wrover cam module for monitoring military headquarters and vital objects - Jatiyoso, Hero Benta; Riadi, M. Farrel; Atturoybi, Abdurrosyid; Mardamsyah, Adam; Tjahjadi, Hendrana (Institute of Computer Science (IOCS), 2025)
Military headquarters security requires advanced systems to detect intrusions and ensure real-time monitoring. This study proposes an IoT-integrated security system using PIR sensors and an ESP-32 WROVER Cam module, designed to enhance detection accuracy, automate alerts, and improve remote surveillance capabilities. The system integrates a PIR sensor for motion detection, an ESP-32 Cam for image capture, and IoT protocols for real-time data transmission via Telegram. A LoRa module extends communication range for large-scale military environments. Simulations tested response time, detection accuracy, and notification reliability under varying conditions. The system achieved a response time of 1.1–1.6 seconds, 100% buzzer activation for alarms, and consistent Telegram notification delivery. Compared to existing systems, its key innovation lies in combining low-cost hardware with IoT connectivity and LoRa-based long-range communication (up to 20–30 km), enabling efficient threat detection and remote interaction. This approach offers a scalable, energy-efficient solution for military security, outperforming traditional systems through real-time responsiveness, reliable alerts, and secure data transmission. The integration of IoT and LoRa addresses gaps in existing object detection systems, particularly in large-area surveillance.